2009
DOI: 10.1097/brs.0b013e3181a95ad2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cell Proliferation Zones, Progenitor Cells and a Potential Stem Cell Niche in the Intervertebral Disc Region

Abstract: BrdU positive cells were found in comparable numbers at early and late time points in most regions of the anulus fibrosus (AF) and nucleus pulposus demonstrating slow ongoing cell proliferation. In the AF border to ligament zone (AFo) and the perichondrium region (P) a stem cell niche-like pattern was determined (a high number of BrdU positive cells at early time points vs. only a few label retaining cells at later time points). In normal and DD tissue from the 4 investigated species progenitor cell markers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 49 publications
11
144
3
1
Order By: Relevance
“…The expression of these markers decreased during aging, but if they are present in mature discs (>18 years), especially galectin-3, this could facilitate disc degeneration. This finding contradicts previous studies, as notochordal cells have a pivotal role in tissue development and regeneration (Henriksson et al, 2009;Minogue et al, 2010b;Pattappa et al, 2012;Risbud et al, 2010;Sakai et al, 2009). Like the cellular response to hydrostatic pressure, in vitro models of NP cells might not reflect in vivo conditions regarding cell-tissue interaction and consequent notochordal cell behavior.…”
Section: Cellular Differentiationcontrasting
confidence: 56%
“…The expression of these markers decreased during aging, but if they are present in mature discs (>18 years), especially galectin-3, this could facilitate disc degeneration. This finding contradicts previous studies, as notochordal cells have a pivotal role in tissue development and regeneration (Henriksson et al, 2009;Minogue et al, 2010b;Pattappa et al, 2012;Risbud et al, 2010;Sakai et al, 2009). Like the cellular response to hydrostatic pressure, in vitro models of NP cells might not reflect in vivo conditions regarding cell-tissue interaction and consequent notochordal cell behavior.…”
Section: Cellular Differentiationcontrasting
confidence: 56%
“…Previous in vitro studies suggested that the intervertebral disc is a tissue with small cell proliferation and regeneration capacity both in annulus fibrosus and nucleus pulposus [44][45][46]. Cell proliferation and regeneration capacity can be increased by external stimulation to promote the restoration of intervertebral discs.…”
Section: Discussionmentioning
confidence: 99%
“…Using a panel of markers validated by the International Society for Cell Therapy as bone marrow MSC markers (CD90?, CD73?, CD105?, CD166?, CD45-, CD34-, CD14-, HLA-DR-), Risbud and colleagues [65] identified cells within human degenerate discs, that were capable of undergoing differentiation along the chondro-, osteo-and adipogenic lineages, while Blanco and colleagues [66] identified cells capable of chondro and osteogenic differentiation. Using BrdU labelling, Henriksson and colleagues [67] located in vivo a population of progenitor cells in the AF border that showed proliferation in a stem cell niche-like pattern.…”
Section: T (Brachyury) Ratmentioning
confidence: 99%